Evaluation of Bactec Mycosis IC/F and Plus Aerobic/F Blood Culture Bottles for Detection of Candida in the Presence of Antifungal Agents - Köck, Robin (American Society for Microbiology, 2013)
Clinical practice guidelines recommend performing follow-up cultures for patients with candidemia in order to determine the time when Candida is cleared from the bloodstream. Since this requires culturing blood samples from patients undergoing antifungal treatment, we evaluated two blood culture bottles (the Bactec Mycosis IC/F [MICF], specifically adapted to the growth of fungi, and the Bactec Plus Aerobic/F [PAF], containing resins to inactivate anti-infective agents) for their effectiveness in detecting Candida albicans and Candida glabrata when seeded in concentrations of 1 CFU/ml and 10 CFU/ml, respectively, together with human whole blood and various antifungal agents in therapeutic peak serum concentrations (C(max)). Significant differences between the MICF and PAF vials for the detection of Candida spp. were found when inoculated with caspofungin (0/12 versus 8/12) (P < 0.001) or amphotericin B (3/12 versus 12/12) (P < 0.001). Inoculation of fluconazole or voriconazole did not influence the effectiveness of detection in the MICF and PAF bottles (P = 1.0). Neither the MICF nor the PAF bottles detected Candida spp. reliably when seeded together with anidulafungin (1/12 versus 1/12) (P = 1.0) or micafungin (0/12 versus 1/12) (P = 1.0). The times to positivity of both bottles were significantly prolonged when antifungal agents were added compared to those of controls without antimycotic drugs (P < 0.001). Overall, the results of this in vitro study indicate that the PAF bottles detected Candida spp. more reliably than the MICF bottles when supplemented with certain antifungal agents. Consequently, clinical studies should evaluate whether this holds true when blood cultures from patients undergoing antifungal treatment are performed.